(3TQM Led GdRLGLis - (3CHh ESMGb EHQGgje Hf CMeO GdZGabis; (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B377 (3g`s
(3ChdgG (B:s
(3GdCbSGe gi GdCLRGA hGMOgG bSe hGdcdGe gh GddaX GdeQcH GdeajO HGdhVY hbhdg (B: (3LGA deYfi JMQR Hg ef MQha GdgLGA s
(3BNQgG (B:s
(3hbdge ai Hfi GdYfHQ (B: (3HdYfHQ , jaYdhf gPG ai cd bHjdI JXgQ eYgG dGe GdJYQja aEf cGfJ eOYeI fMh Hfi GdfLGQ adGjLhR ajg Pdc ced GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(22(3b(B) s
Keywords: (3GdfMhs